PEMETAAN WILAYAH BERDASARKAN PERTUMBUHAN EKONOMI DAN PERSENTASE PENDUDUK MISKIN KABUPATEN/KOTA DI PROVINSI SULAWESI UTARA - Adrianus ., Maabuat; Theodora M. Katiandagho; O. Esry H. Laoh (Sam Ratulangi University, 2016)
The purpose of this research is to describe the mapping of North Sulawesi province based on the economic growth and the percentage of poverty in the regencies and the cities. This research was conducted over four months during January to April 2016. The data that used in this research is secondary data which gathered from Central Bureau Statistics. The analysis that used in this research is descriptive analysis which describe in table and quadrant based on number of economic growth and the percentage of poverty.The results of this research concluded that Sangihe and Talaud Islands Regency are the areas that have not experienced the changing over 2010 â€“ 2014. The Regency of Sitaro Island in 2010-2014 succeeds to maintain the economic growth and the percentage of poverty above average. Kotamobagu and North Minahasa regency was able to sustain the economic growth above the average and poverty below the average during 2010-2014, regencies experienced the changing in quadrant position of economic growth and percentage of poverty during 2010-2014. â€œerâ€